2017
DOI: 10.1016/j.atmosenv.2017.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously reducing CO2 and particulate exposures via fractional recirculation of vehicle cabin air

Abstract: Prior studies demonstrate that air recirculation can reduce exposure to nanoparticles in vehicle cabins. However when people occupy confined spaces, air recirculation can lead to carbon dioxide (CO2) accumulation which can potentially lead to deleterious effects on cognitive function. This study proposes a fractional air recirculation system for reducing nanoparticle concentration while simultaneously suppressing CO2 levels in the cabin. Several recirculation scenarios were tested using a custom-programmed HVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…This suggests a long operation of recirculation mode can lead to poor ventilation. Similar results were found by Jung et al [20]. They determined AER as a function of recirculation door opening percentage.…”
Section: Static Test Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…This suggests a long operation of recirculation mode can lead to poor ventilation. Similar results were found by Jung et al [20]. They determined AER as a function of recirculation door opening percentage.…”
Section: Static Test Resultssupporting
confidence: 88%
“…The slope is equal to -Q l /V c , where Q l is the body leakage flow and V c is the cabin volume. In addition, Jung et al [20] showed…”
Section: Static Test Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since automotive industries aim to decrease energy consumption and the thermal environment of the vehicle has a direct influence on the energy consumption of the HVAC system. A study on quality improvement of vehicular HVAC system was made by Jung et al [8] by performing several air recirculation scenarios. Fojtlin et al [9] developed an automatic control system to accurately capture the thermal environment for the asymmetric and dynamic nature of a car cabin.…”
Section: Introductionmentioning
confidence: 99%